Construction of a ferroptosis scoring system and identification of LINC01572 as a novel ferroptosis suppressor in lung adenocarcinoma - Hong, Lingling; Wang, Xuehai; Cui, Weiming; Wang, Fengxu; Shi, Weiwei; Yu, Shali; Luo, Yonghua; Zhong, Lixin; Zhao, Xinyuan (Frontiers in Pharmacology, 2023)
Background: Ferroptosis is a novel process of programmed cell death driven by excessive lipid peroxidation that is associated with the development of lung adenocarcinoma. N6-methyladenosine (m6a) modification of multiple genes is involved in regulating the ferroptosis process, while the predictive value of m6A- and ferroptosis-associated lncRNA (FMRlncRNA) in the prognosis of patients remains with LUAD remains unknown. Methods: Unsupervised cluster algorithm was applied to generate subcluster in LUAD according to FMRlncRNA. Stepwise Cox analysis and LASSO algorithm were applied to develop a prognostic model. Cellular location was detected by single-cell analysis. Also, we conducted GSEA enrichment, immune microenvironment and drug sensitivity analysis. In addition, the expression and function of the LINC01572 were investigated by several in vitro experiments including qRT-PCR, cell viability assays and ferroptosis assays. Results: A novel FMRlncRNAs-based molecular subtype containing two subclusters were determined in LUAD. Then, we successfully created a risk model according to five FMRlncRNAs (LINC00472, MBNL1-AS1, LINC01572, ZFPM2-AS1 and TMPO-AS1). Our nominated model had good stability and predictive function. The expression patterns of five FMRlncRNAs were confirmed by PCR in LUAD cell lines. Knockdown of LINC01572 significantly inhibited cell viability and induced ferroptosis in LUAD cell lines. Conclusion: Our data provided a risk score system based on FMRlncRNAs with prognostic value in LUAD. Moreover, LINC01572 may serve as a novel ferroptosis suppressor in LUAD.